Mode of action of pamamycin in Staphylococcus aureus. - Chou, W G (1981)
Pamamycin was previously identified as a stimulator of aerial mycelium formation in Streptomyces alboniger and as a new antibiotic. Studies in Staphylococcus aureus grown in brain heart infusion broth showed that this antibiotic was bacteriostatic at 0.1 to 0.3 U/ml and bactericidal at 0.5 U/ml or higher. At concentrations which inhibited growth ca. 40%, pamamycin inhibited the uptake of nucleosides and Pi, as well as purine and pyrimidine bases, and the incorporation of these precursors into nucleic acids. Under the same conditions, the antibiotic had no effect on protein and cell wall synthesis, glucose utilization, or the uptake of amino acids, 2-deoxyglucose, or Mn2+. Further studies suggested that the primary action of pamamycin was on transport processes rather than de novo ribonucleic acid and deoxyribonucleic acid synthesis. Direct in vitro studies of nucleoside transport with isolated membrane vesicles confirmed this conclusion. Pamamycin bound tightly to bacterial membranes and induced significant release of ultraviolet-absorbing material at bactericidal concentrations. It was concluded that the mechanism of growth inhibition involves alteration of membrane-associated cellular functions. Inhibition of Pi transport is a likely primary target for this effect.